Investigation of Speech Impairments in A Child with HIV: The Study of Phonological Processes: Case Report - Zahra ilkhani; Bijan Shafiei; Morteza Farazi (Shiraz University of Medical Sciences, 2017)
Human immunodeficiency virus (HIV) is a viral disease with immunodeficiency in human. So, it can involve different areas such as language, speech, motor and memory. The present research, as a case report, introducing the characteristics of phonological processes of a child who had Aids and lived in a nursery through referring and professional assessing in a speech therapy clinic. The child was a 4 year old boy who was in HIV base on blood test. Speech skills was assessed based on DEAP and language assessment was analyzed according to TOLD-P3. He talked with single word. He used two words sentences rarely. According to language assessment (TOLD-P3), semantic, syntax and phonology features were tested. So he was in emerging language stage. Also his expressive language was lower than his perceive language. In addition, based on DEAP-P test, phonological process of substitution type has been recognized most. Also, the most of the substitution phonological process which accrued have been velar fronting. This study showed that the most phonological process in a child with HIV was the process of substitution. It may be a risk factor for decreasing speech intelligibility. With regard to the results of the present research that showed that the subject had the disorder and there are limited researches in this area, it needs more surveys to help therapists to make a priority in therapeutic stages.